The use of immunotherapy for the treatment of refractory forms of Hodgkin lymphoma in real clinical practice. - I. A. Kamaeva; I. B. Lysenko; N. V. Nikolaeva; T. F. Pushkareva; E. A. Kapuza; Ya. S. Gaisultanova; A. V. Velichko (Южно-Российский онкологический журнал)
With a frequency of 2.2 cases per 100,000 population in Russia, Hodgkin's lymphoma (HL) is one of the most common malignant neoplasms in young people. In connection with the predominant spread of HL among young people, the issue of effective treatment of various forms of HL remains relevant. Currently, 70-90 % of patients with HL who have received standard chemotherapy or chemoradiotherapy have a long period of remission. However, 10 % of patients with progressive course, can`t achieve a response, and 30 % of patients subsequently recur. The standard approach of treating recurrent and/or refractory HL after initial treatment is “salvage therapy” followed by consolidation with high-dose chemotherapy and stem cell transplantation. Although there is a model for treating these patients, recent research has focused on improving the effectiveness and tolerability of rescue therapy. The use of anti- PD-1 drugs opens up new possibilities for the treatment of recurrent/refractory HL. The article describes the results of using checkpoint inhibitors for patients with a history of multi- course chemotherapy. Inhibitors of immune check points were supplemented in the 3rd and subsequent lines of ChT. A clinical case with immunotherapy supplementation in a patient with severe comorbidity is also presented.